1987
DOI: 10.1080/09553008714552301
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Field Strength and Abnormal Development in Chick Embryos Exposed to 50 Hz Magnetic Fields

Abstract: Chick embryos were exposed to sinusoidally oscillating 50 Hz magnetic fields during their first 2 days of development. In the first series of experiments magnetic field strengths of 0.1, 0.3, 1 and 10 A/m were used. The percentage of abnormal embryos (% AE) was 16 per cent in the sham-exposed control group. % AE was increased at 1 A/m (29 per cent) and 10 A/m (32 per cent), but not at 0.1 A/m (16 per cent) or 0.3 A/m (14 per cent). In the second series of experiments field strengths of 0.4, 0.6, 0.9 and 1.35 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…These values agree fairly well with the experimental data suggesting a threshold of 1 A im for the effects on chick embryos (20). The exposure of operators of video display terminals is usually lower (0.1-0.3 A im), but direct comparison to 50-Hz field strengths may be misleading because of the differences in waveform and frequency.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These values agree fairly well with the experimental data suggesting a threshold of 1 A im for the effects on chick embryos (20). The exposure of operators of video display terminals is usually lower (0.1-0.3 A im), but direct comparison to 50-Hz field strengths may be misleading because of the differences in waveform and frequency.…”
Section: Discussionsupporting
confidence: 80%
“…Th e effec ts of loo-Hz sinusoidal field s with a field strength of I Aim were co nfirmed in experiments with a large numb er of eggs (19). Further experi ments wit h 50 Hz confir med that there is an effect at this frequency, too , and suggest ed th at the field strength-response curve has a sharp th reshold at I A im (20).…”
Section: Studies Using Non Mammalian Modelsmentioning
confidence: 79%
See 1 more Smart Citation
“…The magnetic ®eld of % 25 mT was produced by sets of rectangular coils similar to that reported by Juutilainen et al [1987]. Details of the experimental set up have been recently reported by Al-Akhras et al [2001].…”
Section: Methodsmentioning
confidence: 99%
“…Concern in the public over this issue persists, in part due to media accounts of the few but not easily explained reports of an association, but also because of continuing reports of animal experiments Juutilainen et al, , 1987Frolen et al, 1987;Tribukait et al, 1987;Martin, 1988;Blackman et al, 1988;Berman et al, 1990;Zimmerman et al, 1990;Sisken and Guarnieri, 19911, although negative or inconclusive results have also been reported [Kowalczuk et al, 19921. While animal results are not necessarily readily translatable to humans and some results have been seen to be strongly dependent on the exposure conditions and even on the animal strain [Berman et al, 19901, some effects have been observed in different animal species.…”
Section: Resultsmentioning
confidence: 94%